Factors Affecting Quality of Life in Liver Transplant Candidates: An Observational Study - Ana Isabel López-Lazcano; Hugo López-Pelayo; Antoni Gual; Anna Lligoña; Vanessa Vilas-Riotorto; Elsa Caballeria; Pol Bruguera; Luis Pintor (Transplantology, 2021)
Health-related quality of life (HRQOL) before and after liver transplant (LT) is an important outcome in LT candidates as, in these patients, HRQOL is commonly impaired. However, evidence regarding factors that influence HRQOL in patients with end-stage liver disease is inconclusive. The aim of the present study was to identify factors associated with poor HRQOL. An observational study was conducted over LT candidates. The 36-item Short Form Health Survey (widely used to assess HRQOL) and the Hospital Anxiety and Depression Scale were administered to 211 patients during the pre-transplant assessment. Baseline demographic and clinical data were also collected. Multiple regression analysis was performed to investigate risk factors for poor HRQOL. Female sex (lower B = 7.99 95%C = 0.07–15.92, higher B = 18.09 95%CI = 7.56–28.62), encephalopathy (lower B = −9.45, 95%CI = −14.59–−4.31, higher B = −6.69, 95%CI = −13.13 to −0.25), higher MELD scores (lower B = −1.14, 95%CI = −1.67 to −0.61, higher B = −0.33, 95%CI = −0.65 to −0.12), anxiety (lower B = −3.04 95%C = −4.71 to −1.36, higher B = −1.93 95%CI = −3.39 to −0.47)and depression (lower B = −3.27 95%C = −4.46 to −2.08, higher B = −1.02 95%CI = −1.90 to −0.13) symptoms were associated to poorer HRQOL. Psychosocial interventions should be addressed to liver transplant candidates, especially to women, patients with anxiety, depression or episodes of encephalopathy, in order to prevent the impact that these conditions can have on HRQOL.